MODELING HETEROGENEOUS ENVIRONMENT AND MOBILE OBJECTS SUPERVISION IN MONITORING PROBLEMS - A. I. Kuzmich; V. V. Krasnoproshin (Informatika)
A variant of monitoring problem formalization on the basis of the decision theory is considered. The models of heterogeneous environment and mobile heterogeneous object are offered as a structuralinformative basis for solving typical monitoring tasks, including identification, supervision, evaluation, synthesis of control decisions and prognosis. The models aim at practical application and implementation in any modern object-oriented programming language.